2019
DOI: 10.1158/0008-5472.can-18-3376
|View full text |Cite
|
Sign up to set email alerts
|

YES1 Is a Targetable Oncogene in Cancers Harboring YES1 Gene Amplification

Abstract: Targeting genetic alterations of oncogenes by moleculartargeted agents (MTA) is an effective approach for treating cancer. However, there are still no clinical MTA options for many cancers, including esophageal cancer. We used a short hairpin RNA library to screen for a new oncogene in the esophageal cancer cell line KYSE70 and identified YES proto-oncogene 1 (YES1) as having a significant impact on tumor growth. An analysis of clinical samples showed that YES1 gene amplification existed not only in esophageal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 48 publications
1
43
0
Order By: Relevance
“…The ability of a specific CDK8/19 kinase inhibitor, CCT251545, inhibits Wnt pathway-induced tumours in mouse models [ 225 ]. Similarly, another kinase, YES1, implicated in YAP dependent β-catenin transcriptional output, can be inhibited by CH6953755 to restrict YES1-YAP1-dependent tumour growth [ 94 , 226 ]. Lastly, NSC48300, a pharmacologic inhibitor for Taspase1, can effectively inactivate breast and brain tumour growth via preventing the formation of a mature MLL1 complex [ 227 ].…”
Section: Therapeutic Strategymentioning
confidence: 99%
“…The ability of a specific CDK8/19 kinase inhibitor, CCT251545, inhibits Wnt pathway-induced tumours in mouse models [ 225 ]. Similarly, another kinase, YES1, implicated in YAP dependent β-catenin transcriptional output, can be inhibited by CH6953755 to restrict YES1-YAP1-dependent tumour growth [ 94 , 226 ]. Lastly, NSC48300, a pharmacologic inhibitor for Taspase1, can effectively inactivate breast and brain tumour growth via preventing the formation of a mature MLL1 complex [ 227 ].…”
Section: Therapeutic Strategymentioning
confidence: 99%
“…Several lines of evidence indicate that YAP1 is an oncogene. YAP1 was found to act as oncogenic target of 11q22 amplification in multiple cancer subtypes, whereas YAP1 silencing significantly decreases cell proliferation (Lorenzetto et al, 2014, Hamanaka et al, 2019. YAP1 was shown to promote growth of prostate cancer, whereas knock down of its expression or inhibition of YAP1 function significantly suppressed tumor recurrence (Jiang et al, 2017).…”
Section: Yes-associated Protein 1 Encoded By the Yap1 Genementioning
confidence: 99%
“…YES1, as a member of the SRC family, acts as an oncogene in most tumors 30 and plays an important role in the acquired drug resistance of breast and lung cancer 31,32 . This study found that YES1 is signi cantly overexpressed in HB.…”
Section: Discussionmentioning
confidence: 99%